2004
DOI: 10.4319/lom.2004.2.160
|View full text |Cite
|
Sign up to set email alerts
|

A physicochemically constrained seawater culturing system for production of benthic foraminifera

Abstract: We present an apparatus and procedure for culturing deep‐sea (i.e., bathyal) benthic foraminifera under physicochemically constrained conditions. A 1600‐L recirculating culture system was constructed to contribute negligible trace metal contamination; the system was housed in an environmental room maintained near in situ temperatures but at atmospheric pressure. Peristaltic pumps continuously circulated 3 mL seawater min−1 from the reservoir to 9 to 12 culture chambers. A 2‐mm‐thick layer of high‐purity clay‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
1
40
0
1
Order By: Relevance
“…De Nooijer et al (2007) also report that Cu binding to calcein is negligible. Hintz et al (2004) argue that measured Mg/Ca ratios in calcein labelled chambers were of the same magnitude as the ratios in unlabelled chambers. Similarly, showed that calcein does not affect the incorporation of the elements Mg and Sr into foraminiferal calcite.…”
Section: Considerations Of Experimental Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…De Nooijer et al (2007) also report that Cu binding to calcein is negligible. Hintz et al (2004) argue that measured Mg/Ca ratios in calcein labelled chambers were of the same magnitude as the ratios in unlabelled chambers. Similarly, showed that calcein does not affect the incorporation of the elements Mg and Sr into foraminiferal calcite.…”
Section: Considerations Of Experimental Uncertaintiesmentioning
confidence: 99%
“…Although Lu and Allen (2002) report that Cu incorporation competes with Mg and Ca (its incorporation is reduced at increased Ca and/or Mg concentrations), Hintz et al (2004) as well as suggest that the (trace) element incorporation is not affected by the use of calcein. De Nooijer et al (2007) also report that Cu binding to calcein is negligible.…”
Section: Considerations Of Experimental Uncertaintiesmentioning
confidence: 99%
“…After their classification, the selected specimens were exposed to calcein-stained seawater (4 mg l -1 ) for 2 wk (Bernhard et al 2004, Barras et al 2009) and then placed into 300 ml transparent polycarbonate culture vessels, 30 specimens to a vessel. Each vessel contained 10 small active, 10 larger active and 10 large inactive specimens (Fig.…”
Section: Samplingmentioning
confidence: 99%
“…Experimental setup. Culturing of Ammonia aomo riensis was performed in a flow-through system following the concept of Hintz et al (2004) (Fig. 1).…”
Section: Samplingmentioning
confidence: 99%
“…Since it is notoriously difficult to culture deep-sea benthic foraminifera in the laboratory under insitu conditions, culture experiments are often limited to shallowwater species (Chandler et al, 1996), or specimen taken from water depths shallower than 250 m (Wilson-Finelli et al, 1998;Havach et al, 2001). Culturing systems like those developed by Hintz et al (2004) have allowed for systematic experiments on deep sea benthic foraminifera (Nomaki et al, 2005(Nomaki et al, , 2006McCorkle et al, 2008;Barras et al, 2010;Filipsson et al, 2010). From a theoretical point of view, progress has mostly been made on planktonic foraminifera Zeebe et al, 1999).…”
Section: Introductionmentioning
confidence: 99%